Evaluating image-derived input functions for cerebral [18F]MC225 PET studies - Salvi de Souza, Giordana; Mossel, Pascalle; Somsen, Joost F.; Providência, Laura; Bartels, Anna L.; Willemsen, Antoon T. M.; Dierckx, Rudi A. J. O.; Furini, Cristiane R. G.; Lammertsma, Adriaan A.; Tsoumpas, Charalampos; Luurtsema, Gert (Frontiers in Nuclear Medicine, 2025)
Kinetic modelling of brain PET data is crucial for estimating quantitative biological parameters, traditionally requiring arterial sampling. This study evaluated whether arterial samples could be omitted to estimate the image-derived input function (IDIF) using a long axial field-of-view PET scanner. The use of internal carotid arteries (ICA) for IDIF estimation, along with venous samples for plasma-to-whole blood ratios and plasma parent fractions, was also assessed. Six healthy volunteers underwent [18F]MC225 scans with manual arterial sampling. IDIFs were derived from the aortic arch (IDIFAA) and calibrated using manual arterial samples (IDIFAA_CAL). ICA-derived IDIF was also calibrated (IDIFCA_CAL) and compared to IDIFAA_CAL. In a separate group of six volunteers, venous and arterial samples were collected to evaluate plasma-to-whole blood ratios, plasma parent fractions, and IDIF calibration (IDIFCA_CAL_VEN). Volume of distribution (VT) of different brain regions was estimated for all IDIFs techniques, corrected for plasma-to-whole blood ratio and plasma parent fraction (IDIFAA,P, IDIFAA_CAL,P, IDIFICA_CAL,P and IDIFICA_CAL_VEN_P). Our findings revealed discrepancies between IDIFAA and arterial samples, highlighting the importance of calibration. The differences between IDIFAA,P and IDIFAA_CAL,P were 9.2% for area under the curve and 4.0% for brain VT. IDIFICA_CAL,P showed strong agreement with IDIFA_CAL,P, with 1.2% VT difference. Venous sampling showed consistent agreement with arterial sampling for plasma parameters but was unreliable for IDIF calibration, leading to 39% VT differences. This study emphasises that arterial samples are still required for IDIF calibration and reliable VT estimation for [18F]MC225 PET tracer. ICA-derived IDIF, when calibrated, provides reliable VT estimates. Venous sampling is a potential alternative for estimating plasma parameters, but it is unsuitable for IDIF calibration.Trial RegistryNCT05618119 (clinicaltrials.gov/study/NCT05618119).